Playwrights for Tomorrow : A Collection of Plays, Volume 6 - Ballet, Arthur H. (Book collections on Project MUSE., 2014)
Playwrights for Tomorrow was first published in 1969. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Three plays are published in this sixth volume of a series of collections of plays by dramatists who have participated in an experimental program conducted by the Office for Advanced Drama Research (O.A.D.R.), University of Minnesota. Dr. Arthur H. Ballet, editor of the series, is the director of the program. The plays in this volume are The Thing Itself by Arthur Sainer, The Marriage Test by Jonathan Gillman, and The End of the World; or, Fragments from a Work in Progress by Keith Neilson. In an introduction Dr. Ballet briefly describes the O.A.D.R. program and comments on the three plays. Of Mr. Sainer and his play Dr. Ballet writes: "Arthur Sainer represents a new wave in theatrical writing, the semi-improvisational piece which really takes on life only in production, but which also speaks with a voice as old and honorable as theatre itself. The Firehouse Theatre, with its unique and skillful dedication to innovative theatre, brought The Things Itself to exciting production for enthusiastic audiences." Jonathan Gillman's The Marriage Test is, he writes, "a rare and sparkling work for the stage: a classic farce." On the third play and its author he comments: "The End of the World by Keith Neilson was the first play provided with facilities under the O.A.D.R. outside the Minneapolis-St. Paul area in an attempt to see if the program could work at long distance as well as it has at home. The play, the playwright, and the O.A.D.R. were blessed with a wonderful company, theatre, and audience at the Playhouse in the Park, Cincinnati, Ohio, and above all with a dedicated and talented director in Brooks Jones. Neilson is a continuous creator in theatre."